In vitro colonic fermentation of dietary fibers: Fermentation rate, short-chain fatty acid production and changes in microbiota - Wang, Miaomiao; Wichienchot, Santad; He, Xiaowei; Fu, Xiong; Huang, Qiang; Zhang, Bin (Trends in food science & technology, 2019)
Dietary fiber is the undigested carbohydrate that escapes small intestinal digestion and absorption, and then reaches the large intestine for partial or complete fermentation by the colonic microbiota. Fermentation of dietary fiber into short-chain fatty acids (i.e., acetic, propionic, and butyric particularly) in the colon has been reported to bring about positive changes in microbiota composition and reduce the risk of colon-related diseases as well as some metabolic syndromes, such as obesity, diabetes, chronic kidney disease, and systemic inflammation. There is a growing interest in the fate of different dietary fibers in the gastrointestinal tract regarding their rate and extent (location) of fermentation and microbiota changes, particularly from data obtained with static and dynamic in vitro models. These models provide information on the fermentation performance and microbiota modulation by dietary fibers with diverse structures and enable the formulation of functional foods with health benefits. This review summarizes the fermentation performance of various dietary fibers using in vitro models. Both the physical and chemical structures of dietary fibers are critical factors that determine fermentation rate, short-chain fatty acid profiles and growth of different bacterial groups. Considering the potential relationship between fermentation performance and health, three principles for designing fermentable dietary fiber are proposed: slow fermentation in the colon; high butyrate and/or propionate production; and selective bacterial growth, promoting the beneficial bacteria that improve the intestinal barrier function. •Advantages and disadvantages of static and dynamic in vitro fecal fermentation models.•Summary of fermentation performance and microbiota modulation of various dietary fibers using in vitro models.•Three principles for designing fermentable dietary fiber are proposed.